Niche dynamics of alien species do not differ among sexual and apomictic flowering plants. Issue 3 (28th October 2015) - Dellinger, Agnes S.; Essl, Franz; Hojsgaard, Diego; Kirchheimer, Bernhard; Klatt, Simone; Dawson, Wayne; Pergl, Jan; Pyšek, Petr; van Kleunen, Mark; Weber, Ewald; Winter, Marten; Hörandl, Elvira; et al.
Summary: Biological invasions can be associated with shifts of the species' climatic niches but the incidence of such shifts is under debate. The reproductive system might be a key factor controlling such shifts because it influences a species' evolutionary flexibility. However, the link between reproductive systems and niche dynamics in plant invasions has been little studied so far. We compiled global occurrence data sets of 13 congeneric sexual and apomictic species pairs, and used principal components analysis (PCA) and kernel smoothers to compare changes in climatic niche optima, breadths and unfilling/expansion between native and alien ranges. Niche change metrics were compared between sexual and apomictic species. All 26 species showed changes in niche optima and/or breadth and 14 species significantly expanded their climatic niches. However, we found no effect of the reproductive system on niche dynamics. Instead, species with narrower native niches showed higher rates of niche expansion in the alien ranges. Our results suggest that niche shifts are frequent in plant invasions but evolutionary potential may not be of major importance for such shifts. Niche dynamics rather appear to be driven by changes of the realized niche without adaptive change of the fundamental climatic niche.